Environment-friendly plastic and preparation method thereof

By combining polyvinyl alcohol with nanoorganic bentonite and embedded in thermoplastic elastomers, the problem that the addition of polyvinyl alcohol in thermoplastic elastomers is solved, and the efficient biodegradation and environmental performance of the material are improved.

CN119286275AInactive Publication Date: 2025-01-10HUNAN JUNHAO ENERGY SAVING & ENVIRONMENTAL PROTECTION TECHNOLOGY CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411517472.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-01-10
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The addition of polyvinyl alcohol to existing thermoplastic elastomers is difficult to improve biodegradation capabilities, and the degradation performance is affected due to compatibility problems and water absorption processes.

Method used

Polyvinyl alcohol is combined with nanoorganic bentonite to form composite nanoorganic bentonite and embedded in thermoplastic elastomers to improve interfacial compatibility and accelerate the biodegradation process.

Benefits of technology

By embedding the polyvinyl alcohol molecular chain between the nanoorganic bentonite layers, the moisture permeation and expansion process is enhanced, and the biodegradation and environmental protection properties of the material are significantly improved.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of high polymer materials. The invention relates to plastic, in particular to environment-friendly plastic and a preparation method thereof. The product prepared by the invention comprises thermoplastic elastomer matrix resin and polyvinyl alcohol composite nano organic bentonite, the mass ratio of the thermoplastic elastomer matrix resin to the polyvinyl alcohol composite nano organic bentonite is 10: (1-1.2); wherein in the polyvinyl alcohol composite nano organobentonite, at least part of polyvinyl alcohol resin is embedded between layers of the nano organobentonite; the mass ratio of the polyvinyl alcohol resin to the nano organic bentonite is 1: (10-12); the polyvinyl alcohol composite nano organic bentonite is a sphere-like particle, and the D50 of the sphere-like particle is 2-4 [mu] m; the sphericity degree of the sphere-like particles is 8.5 to 9.0.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of polymer materials and more specifically relates to an environmentally friendly plastic and a preparation method thereof. Background Art

[0002] Thermoplastic elastomer (TPE) is a material that has the characteristics of both rubber and thermoplastics. It has high elasticity of rubber at room temperature and can be re-plasticized at high temperature. TPE has the characteristics of environmental protection, non-toxicity and safety, wide hardness range, excellent colorability, soft touch, weather resistance, fatigue resistance and temperature resistance. It has excellent processing performance, does not require vulcanization, can be recycled, reduces costs, and can be coated and bonded with a variety of base materials or formed alone.

[0003] Adding biodegradable resin materials to TPE resin can indeed improve the biodegradability of TPE resin; for example, adding polyvinyl alcohol resin. However, the combination of the two is also prone to some new problems. For example, compatibility issues may lead to uneven microstructure of the blend and affect its degradation rate; due to the presence of TPE, it may form an incompatible phase with polyvinyl alcohol resin, which may cause changes in the crystallization behavior and degradation path of polyvinyl alcohol, thereby affecting its biodegradability.

[0004] Therefore, simple physical blending obviously cannot achieve the desired improvement in biodegradability by introducing an appropriate amount of polyvinyl alcohol resin. Summary of the invention

[0005] The technical problem to be solved by the present invention is that for environmentally friendly plastic products based on thermoplastic elastomers, simply adding degradable resins such as polyvinyl alcohol cannot achieve the desired improvement in degradability. Based on the above problem, the present invention provides an environmentally friendly plastic and a preparation method thereof.

[0006] The purpose of the present invention is to provide an environmentally friendly plastic.

[0007] Another object of the present invention is to provide a method for preparing environmentally friendly plastic.

[0008] The above-mentioned purpose of the present invention is achieved through the following technical solutions:

[0009] An environmentally friendly plastic, comprising: a thermoplastic elastomer matrix resin, polyvinyl alcohol composite nano-organic bentonite;

[0010] The mass ratio of the thermoplastic elastomer matrix resin to the polyvinyl alcohol composite nano-organic bentonite is 10:1-1.2;

[0011] Wherein, in the polyvinyl alcohol composite nano-organic bentonite, at least part of the polyvinyl alcohol resin is embedded in the interlayer of the nano-organic bentonite;

[0012] Furthermore, the mass ratio of the polyvinyl alcohol resin to the nano-organic bentonite is 1:10-12;

[0013] The polyvinyl alcohol composite nano-organic bentonite is spherical particles, and the D50 of the spherical particles is 2-4 um.

[0014] The above technical solution uses thermoplastic elastomer as the base resin of the environmentally friendly plastic, and adds polyvinyl alcohol therein to improve the biodegradability of the thermoplastic elastomer, thereby improving the biodegradability of the product;

[0015] However, the inventors found that if polyvinyl alcohol is directly added, on the one hand, the interfacial compatibility between polyvinyl alcohol and the thermoplastic elastomer resin as the matrix resin is poor; on the other hand, polyvinyl alcohol needs to absorb water to accelerate its degradation process during biodegradation, and after the thermoplastic elastomer and polyvinyl alcohol are mixed, the thermoplastic elastomer will significantly affect the water absorption process of polyvinyl alcohol, thereby making it difficult to obtain the desired biodegradation performance by adding an appropriate amount of polyvinyl alcohol; and long-term inability to degrade will lead to a decrease in the environmental performance of the product;

[0016] Based on this, the inventors compounded polyvinyl alcohol and nano-organic bentonite and added the composite to the thermoplastic elastomer. Specifically, the presence of organic bentonite can improve the interfacial compatibility between polyvinyl alcohol and the matrix resin to a certain extent. In addition, more importantly, the above technical solution embeds part of the polyvinyl alcohol resin into the interlayer of nano-organic bentonite, so that at least part of the molecular chains of the polyvinyl alcohol resin are not bound by the molecular chains of the thermoplastic elastomer. In addition, during the degradation process, when the polyvinyl alcohol molecular chain or the bentonite structure absorbs water, the layered structure of the bentonite will gradually expand as the water molecules continue to erode. This expansion process will allow the water to further diffuse and penetrate into the interior faster, thereby accelerating the biodegradation process of the product. By adopting a spherical structure, the internal stress generated by the expansion process can have a positive effect on the degradation of the resin system at all angles.

[0017] Furthermore, the sphericity of the quasi-spherical particles is 8.5-9.0.

[0018] Furthermore, the polyvinyl alcohol resin is a polyvinyl alcohol resin with an alcoholysis degree of less than 95%.

[0019] Furthermore, the thermoplastic elastomer matrix resin is selected from any one of styrene-based thermoplastic elastomers, polyolefin-based thermoplastic elastomers, polyurethane-based thermoplastic elastomers, polyester-based thermoplastic elastomers, and polyamide-based thermoplastic elastomers.

[0020] Furthermore, the environmentally friendly plastic further comprises: 1.2-1.5% of the weight of the thermoplastic elastomer in the amount of an antioxidant, 2-4% of the weight of the thermoplastic elastomer in the amount of an anti-aging agent, and 3-5% of the weight of the thermoplastic elastomer in the amount of zinc stearate;

[0021] Wherein, the antioxidant is selected from any one of antioxidant BHT, antioxidant 801, butylated hydroxytoluene, and thiobis(3-methyl-6-tert-butyl)phenol;

[0022] The antioxidant is selected from any one of antioxidant 4010, antioxidant RD, antioxidant MB, antioxidant D, antioxidant AW, and antioxidant BLE.

[0023] Furthermore, the nano-organobentonite is selected from any one of quaternary ammonium salt organobentonite, amine-based organobentonite, organic acid-based organobentonite, alcoholamine-based organobentonite and ester-based organobentonite.

[0024] A method for preparing environmentally friendly plastic, the specific preparation steps comprising:

[0025] Preparation of polyvinyl alcohol composite nano-organic bentonite:

[0026] Mixing and dissolving polyvinyl alcohol and water to obtain a polyvinyl alcohol solution;

[0027] After mixing the nano-organic bentonite and water, the mixture is ultrasonically dispersed for 45-60 minutes at a temperature of 80-90° C. and an ultrasonic frequency of 200-220 kHz to obtain a nano-organic bentonite dispersion;

[0028] The polyvinyl alcohol solution and the nano-organic bentonite dispersion are uniformly mixed, spray-dried, and sieved to obtain polyvinyl alcohol composite nano-organic bentonite;

[0029] Preparation of environmentally friendly plastic:

[0030] Thermoplastic elastomer matrix resin and polyvinyl alcohol composite nano-organic bentonite are mixed, heated and kneaded, and then extruded to obtain environmentally friendly plastic.

[0031] Technical effect:

[0032] In the preparation process of the above technical scheme, polyvinyl alcohol and water are first mixed and dissolved, and a relatively large ultrasonic frequency is used for treatment so that the interlayer spacing of the nano-organic bentonite is widened. In the subsequent mixing process, the polyvinyl alcohol solution diffuses and embeds into the interlayers, and then spray drying is used. During the drying process, the composite forms spherical particles, and the layered structure of the organic bentonite is re-stacked. During the stacking process, at least part of the polyvinyl alcohol molecules are effectively embedded inside it.

[0033] Furthermore, the preparation of the polyvinyl alcohol composite nano-organic bentonite also includes:

[0034] After the nano-organic bentonite and water are mixed, an emulsifier of 5-7% of the mass of the nano-organic bentonite is added;

[0035] The emulsifier is selected from any one of sodium dodecylbenzene sulfonate, emulsifier OP-10, Tween-60 and Span-80.

[0036] Furthermore, the spray drying includes: spray drying under the conditions of a feed rate of 100-120 g / min, a main disk rotation speed of 7800-8800 r / min, an inlet air temperature of 140-145°C, and an outlet air temperature of 120-125°C. DETAILED DESCRIPTION

[0037] The present invention is further described below with reference to specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0038] Unless otherwise specified, the reagents and materials used in the following examples are commercially available.

[0039] Example 1

[0040] Preparation of polyvinyl alcohol composite nano-organic bentonite:

[0041] After mixing polyvinyl alcohol and water in a mass ratio of 1:8.5, the mixture was allowed to swell at room temperature for 8 hours, and then stirred and dissolved at 80°C and a stirring speed of 500 r / min for 4 hours to obtain a polyvinyl alcohol solution;

[0042] The polyvinyl alcohol resin is a polyvinyl alcohol resin with an alcoholysis degree of less than 95%;

[0043] After mixing nano-organic bentonite and water in a mass ratio of 1:9, the mixture was ultrasonically dispersed at 80°C and an ultrasonic frequency of 200kHz for 45 minutes to obtain a nano-organic bentonite dispersion.

[0044] According to the mass ratio of polyvinyl alcohol to nano-organic bentonite being 1:10, the polyvinyl alcohol solution and the nano-organic bentonite dispersion are weighed respectively;

[0045] The nano organic bentonite is selected from quaternary ammonium salt organic bentonite;

[0046] The polyvinyl alcohol solution and the nano-organic bentonite dispersion are continuously stirred and mixed for 4 hours at a stirring rate of 800 r / min, and then spray-dried so that at least a portion of the polyvinyl alcohol resin is embedded in the interlayer of the nano-organic bentonite and spherical particles are formed during the spray-drying process, and then sieved to obtain polyvinyl alcohol composite nano-organic bentonite;

[0047] The D50 of the polyvinyl alcohol composite nano-organic bentonite is 2 um;

[0048] The sphericity of the polyvinyl alcohol composite nano-organic bentonite is 8.5;

[0049] The spray drying comprises: spray drying under the conditions of a feed rate of 100 g / min, a main disk speed of 7800 r / min, an inlet air temperature of 140° C., and an outlet air temperature of 120° C.;

[0050] Preparation of environmentally friendly plastic:

[0051] Thermoplastic elastomer matrix resin and polyvinyl alcohol composite nano-organic bentonite are mixed in a mass ratio of 10:1, and 1.2% of the weight of the thermoplastic elastomer antioxidant, 2% of the weight of the thermoplastic elastomer anti-aging agent, and 3% of the weight of the thermoplastic elastomer zinc stearate are added; the mixture is heated and mixed in a torque rheometer at a temperature of 185° C. and a rotation speed of 80 r / min for 10 minutes, and then extruded to obtain an environmentally friendly plastic;

[0052] The thermoplastic elastomer matrix resin is selected from styrene-based thermoplastic elastomers;

[0053] Wherein, the antioxidant is selected from the antioxidant BHT;

[0054] The antioxidant is selected from antioxidant 4010.

[0055] Example 2

[0056] Preparation of polyvinyl alcohol composite nano-organic bentonite:

[0057] After mixing polyvinyl alcohol and water in a mass ratio of 1:8.8, the mixture was allowed to swell at room temperature for 8 hours, and then the mixture was stirred and dissolved at a temperature of 82°C and a stirring speed of 500 r / min for 4 hours to obtain a polyvinyl alcohol solution;

[0058] The polyvinyl alcohol resin is a polyvinyl alcohol resin with an alcoholysis degree of less than 95%;

[0059] After mixing nano-organic bentonite and water in a mass ratio of 1:9.5, the mixture was ultrasonically dispersed at a temperature of 85°C and an ultrasonic frequency of 210kHz for 50 minutes to obtain a nano-organic bentonite dispersion;

[0060] According to the mass ratio of polyvinyl alcohol to nano-organic bentonite being 1:11, the polyvinyl alcohol solution and the nano-organic bentonite dispersion are weighed respectively;

[0061] The nano-organic bentonite is selected from amino-organic bentonite;

[0062] The polyvinyl alcohol solution and the nano-organic bentonite dispersion were continuously stirred and mixed for 4.5 hours at a stirring rate of 800 r / min, and then spray-dried so that at least a portion of the polyvinyl alcohol resin was embedded in the interlayer of the nano-organic bentonite and spherical particles were formed during the spray-drying process, and then sieved to obtain polyvinyl alcohol composite nano-organic bentonite;

[0063] The D50 of the polyvinyl alcohol composite nano-organic bentonite is 3 um;

[0064] The sphericity of the polyvinyl alcohol composite nano-organic bentonite is 8.8;

[0065] The spray drying comprises: spray drying under the conditions of a feed rate of 110 g / min, a main disk speed of 7900 r / min, an inlet air temperature of 142° C., and an outlet air temperature of 123° C.;

[0066] Preparation of environmentally friendly plastic:

[0067] Thermoplastic elastomer matrix resin and polyvinyl alcohol composite nano-organic bentonite are mixed in a mass ratio of 10:1.1, and 1.3% of the weight of the thermoplastic elastomer antioxidant, 3% of the weight of the thermoplastic elastomer anti-aging agent, and 4% of the weight of the thermoplastic elastomer zinc stearate are added; the mixture is heated and mixed in a torque rheometer at a temperature of 188° C. and a rotation speed of 90 r / min for 11 minutes, and then extruded to obtain an environmentally friendly plastic;

[0068] The thermoplastic elastomer matrix resin is selected from styrene-based thermoplastic elastomers;

[0069] Wherein, the antioxidant is selected from antioxidant 801;

[0070] The antioxidant is selected from antioxidant RD.

[0071] Example 3

[0072] Preparation of polyvinyl alcohol composite nano-organic bentonite:

[0073] After mixing polyvinyl alcohol and water in a mass ratio of 1:9.0, the mixture was allowed to swell at room temperature for 8 hours, and then the mixture was stirred and dissolved at a temperature of 85°C and a stirring speed of 500 r / min for 4 hours to obtain a polyvinyl alcohol solution;

[0074] The polyvinyl alcohol resin is a polyvinyl alcohol resin with an alcoholysis degree of less than 95%;

[0075] After mixing nano-organic bentonite and water in a mass ratio of 1:10, the mixture was ultrasonically dispersed at a temperature of 90°C and an ultrasonic frequency of 220kHz for 60 minutes to obtain a nano-organic bentonite dispersion;

[0076] According to the mass ratio of polyvinyl alcohol to nano-organic bentonite being 1:12, the polyvinyl alcohol solution and the nano-organic bentonite dispersion are weighed respectively;

[0077] The nano-organic bentonite is selected from alcoholamine organobentonite;

[0078] The polyvinyl alcohol solution and the nano-organic bentonite dispersion were continuously stirred and mixed for 5 hours at a stirring rate of 800 r / min, and then spray-dried, so that at least part of the polyvinyl alcohol resin was embedded in the interlayer of the nano-organic bentonite, and spherical particles were formed during the spray-drying process, and then sieved to obtain polyvinyl alcohol composite nano-organic bentonite;

[0079] The D50 of the polyvinyl alcohol composite nano-organic bentonite is 4 um;

[0080] The sphericity of the polyvinyl alcohol composite nano-organic bentonite is 9.0;

[0081] The spray drying comprises: spray drying under the conditions of a feed rate of 120 g / min, a main disk speed of 8800 r / min, an inlet air temperature of 145° C., and an outlet air temperature of 125° C.;

[0082] Preparation of environmentally friendly plastic:

[0083] Thermoplastic elastomer matrix resin and polyvinyl alcohol composite nano-organic bentonite are mixed in a mass ratio of 10:1.2, and 1.5% of the weight of the thermoplastic elastomer antioxidant, 4% of the weight of the thermoplastic elastomer anti-aging agent, and 5% of the weight of the thermoplastic elastomer zinc stearate are added; the mixture is heated and mixed in a torque rheometer at a temperature of 190° C. and a rotation speed of 100 r / min for 12 minutes, and then extruded to obtain an environmentally friendly plastic;

[0084] The thermoplastic elastomer matrix resin is selected from styrene-based thermoplastic elastomers;

[0085] Wherein, the antioxidant is selected from butylated hydroxytoluene;

[0086] The antioxidant is selected from antioxidant MB.

[0087] Example 4

[0088] The present embodiment is different from the embodiment 1 in that the polyvinyl alcohol resin is a polyvinyl alcohol resin having an alcoholysis degree greater than 97%, and the other conditions remain unchanged.

[0089] Example 5

[0090] Compared with Example 1, this embodiment is different in that:

[0091] The D50 of the polyvinyl alcohol composite nano-organic bentonite is 6 um;

[0092] The sphericity of the polyvinyl alcohol composite nano-organic bentonite is 8.0;

[0093] The rest of the conditions remain unchanged.

[0094] Comparative Example 1

[0095] Compared with Example 1, this comparative example has the following differences:

[0096] Preparation of polyvinyl alcohol composite nano-organic bentonite:

[0097] According to the mass ratio of polyvinyl alcohol to nano-organic bentonite being 1:10, polyvinyl alcohol and nano-organic bentonite were weighed respectively; polyvinyl alcohol and nano-organic bentonite were then added into water of 8 times the mass of the nano-organic bentonite, and the mixture was stirred and mixed with a stirrer at a speed of 300 r / min for 2 hours, and then evaporated to remove water, and then the mixture was broken up and sieved to obtain polyvinyl alcohol composite nano-organic bentonite with a D50 of 2 um;

[0098] The rest of the conditions remain unchanged.

[0099] Comparative Example 2

[0100] The difference between this comparative example and Example 1 is that:

[0101] Without adding nano-organic bentonite, polyvinyl alcohol is directly added to the thermoplastic elastomer resin. Specifically:

[0102] Thermoplastic elastomer matrix resin and polyvinyl alcohol are mixed in a mass ratio of 10:1, and 1.2% of the weight of the thermoplastic elastomer antioxidant, 2% of the weight of the thermoplastic elastomer anti-aging agent, and 3% of the weight of the thermoplastic elastomer zinc stearate are added; the mixture is heated and mixed in a torque rheometer at a temperature of 185° C. and a rotation speed of 80 r / min for 10 minutes, and then extruded to obtain an environmentally friendly plastic;

[0103] The rest of the conditions remain unchanged.

[0104] The performance tests were performed on the products obtained in Examples 1-5 and Comparative Examples 1-2. The specific test methods and test results are as follows:

[0105] Biodegradation performance test:

[0106] The products obtained in the above-mentioned embodiments and comparative examples were made into slices with a thickness of 3 mm. The slices with a size of 10 cm×10 cm were weighed m1 and buried in moist soil (water content of 25%) by soil burial method. After one month at a temperature of 25° C., the slices were taken out, dried and weighed m2. The degradation performance was characterized by its mass change rate. The detailed test results are shown in Table 1.

[0107] Mass change rate = (m1-m2) / m1×100%;

[0108] Referring to GB / T 1040.1-2018 "Determination of tensile properties of plastics", the tensile properties of the products obtained in the embodiments and comparative examples were tested, and the specific test results are shown in Table 1;

[0109] Table 1: Product performance test results

[0110] Quality change rate / % Tensile strength / MPa Elongation at break / % Example 1 12.2 35.6 520 Example 2 12.4 35.8 532 Example 3 12.5 35.9 538 Example 4 10.9 35.3 495 Example 5 11.3 35.1 488 Comparative Example 1 9.1 34.3 462 Comparative Example 2 8.2 30.2 440

[0111] It can be seen from the test results in Table 1 that the product obtained by the present invention has excellent mechanical properties and good biodegradability.

[0112] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. An environmentally friendly plastic, characterized in that: include: Thermoplastic elastomer matrix resin, polyvinyl alcohol composite nano-organic bentonite; The mass ratio of the thermoplastic elastomer matrix resin to the polyvinyl alcohol composite nano-organic bentonite is 10:1-1.2; Wherein, in the polyvinyl alcohol composite nano-organic bentonite, at least part of the polyvinyl alcohol resin is embedded in the interlayer of the nano-organic bentonite; Furthermore, the mass ratio of the polyvinyl alcohol resin to the nano-organic bentonite is 1:10-12; The polyvinyl alcohol composite nano-organic bentonite is spherical particles, and the D50 of the spherical particles is 2-4 um.

2. The environmentally friendly plastic according to claim 1, characterized in that: The sphericity of the quasi-spherical particles is 8.5-9.

0.

3. The environmentally friendly plastic according to claim 1, characterized in that: The polyvinyl alcohol resin is a polyvinyl alcohol resin with an alcoholysis degree of less than 95%.

4. The environmentally friendly plastic according to claim 1, characterized in that: The thermoplastic elastomer matrix resin is selected from any one of styrene-based thermoplastic elastomers, polyolefin-based thermoplastic elastomers, polyurethane-based thermoplastic elastomers, polyester-based thermoplastic elastomers, and polyamide-based thermoplastic elastomers.

5. The environmentally friendly plastic according to claim 1, characterized in that: The environmentally friendly plastic also includes: 1.2-1.5% of the weight of the thermoplastic elastomer in the antioxidant, 2-4% of the weight of the thermoplastic elastomer in the anti-aging agent, and 3-5% of the weight of the thermoplastic elastomer in the zinc stearate; Wherein, the antioxidant is selected from any one of antioxidant BHT, antioxidant 801, butylated hydroxytoluene, and thiobis(3-methyl-6-tert-butyl)phenol; The antioxidant is selected from any one of antioxidant 4010, antioxidant RD, antioxidant MB, antioxidant D, antioxidant AW, and antioxidant BLE.

6. The environmentally friendly plastic according to claim 1, characterized in that: The nano-organic bentonite is selected from any one of quaternary ammonium salt organic bentonite, amine organic bentonite, organic acid organic bentonite, alcoholamine organic bentonite and ester organic bentonite.

7. A method for preparing the environmentally friendly plastic according to any one of claims 1 to 6, characterized in that: The specific preparation steps include: Preparation of polyvinyl alcohol composite nano-organic bentonite: Mixing and dissolving polyvinyl alcohol and water to obtain a polyvinyl alcohol solution; After mixing the nano-organic bentonite and water, the mixture is ultrasonically dispersed for 45-60 minutes at a temperature of 80-90° C. and an ultrasonic frequency of 200-220 kHz to obtain a nano-organic bentonite dispersion; The polyvinyl alcohol solution and the nano-organic bentonite dispersion are uniformly mixed, spray-dried, and sieved to obtain polyvinyl alcohol composite nano-organic bentonite; Preparation of environmentally friendly plastic: Thermoplastic elastomer matrix resin and polyvinyl alcohol composite nano-organic bentonite are mixed, heated and kneaded, and then extruded to obtain environmentally friendly plastic.

8. The method for preparing an environmentally friendly plastic according to claim 7, characterized in that: The preparation of the polyvinyl alcohol composite nano-organic bentonite also includes: After the nano-organic bentonite and water are mixed, an emulsifier of 5-7% of the mass of the nano-organic bentonite is added; The emulsifier is selected from any one of sodium dodecylbenzene sulfonate, emulsifier OP-10, Tween-60 and Span-80.

9. The method for preparing an environmentally friendly plastic according to claim 7, characterized in that: The spray drying comprises: spray drying under the conditions of a feed rate of 100-120 g / min, a main disk rotation speed of 7800-8800 r / min, an inlet air temperature of 140-145° C., and an outlet air temperature of 120-125° C.

Citation Information

Patent Citations

  • Nano bentonite for modifying plastics and preparation method of nano bentonite

    CN102604162A

  • Polyving alcohol composite hydrogel and preparation method thereof

    CN103665685A

  • Yoga mattress

    CN107312323A

  • Bentonite associated and conpolymerized degradable modified composite material and preparation method thereof

    CN109438634A

  • Elastic nanoparticle composite organic bentonite, preparation method thereof and lubricant

    CN109897717A